Accompagner les étudiants malades à l'université Une médiation au cœur de l'inclusion des étudiants porteurs d'un cancer ou d'une maladie rare - Sivilotti, Lucas (S@nté en contextes, 2022)
This book questions the student's pathways and professionnal positioning related to teenagers and young adults with rare diseases. We have chosen to give voices to users and actors concerned. This book provides a better understanding of the need to be inclusive. It considers the development of mediating interventions taking into account the current organization of services. Those interventions involve all the people participating in the accompaniment of students in higher education. High school and university are not two different worlds. Despite the efforts made to open up, they still work in isolation from each other. The proposed actions aims at decompartmentalizing them in order to establish or re-establish the link between institutions, by accompany young disabled from school to college.